2011
DOI: 10.1007/s00405-011-1652-5
|View full text |Cite
|
Sign up to set email alerts
|

The alternative ear-piercing technique by using superpulsed carbon dioxide laser: a comparative study with spring-loaded gun

Abstract: Ear piercing (EP) is increasing in popularity among teenagers. Techniques for EP should be selected carefully to prevent possible complications. The purpose of this study is to compare the clinical outcomes of EP techniques between CO(2) laser and spring-loaded gun. This is a prospective and comparative clinical trial. Under local anesthesia, EP was performed on left ear with CO(2) laser (20 watt/single mode) and on right ear with spring-loaded gun. With visual analog scale (VAS, 0-10) and questionnaire, post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Accordingly, demands for a safer, standardized method which can be used in piercing has been growing, and CO2 laser has been introduced as an alternative method for ear piercing. 3 It was shown that the severity and duration of pain after ear piercing was less in the CO2 laser pierced group compared to the spring-loaded gun pierced group. 3 Wound healing was also better in CO2 laser treated sites with less scar contraction compared to scalpel wounds.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Accordingly, demands for a safer, standardized method which can be used in piercing has been growing, and CO2 laser has been introduced as an alternative method for ear piercing. 3 It was shown that the severity and duration of pain after ear piercing was less in the CO2 laser pierced group compared to the spring-loaded gun pierced group. 3 Wound healing was also better in CO2 laser treated sites with less scar contraction compared to scalpel wounds.…”
Section: Discussionmentioning
confidence: 93%
“…3 It was shown that the severity and duration of pain after ear piercing was less in the CO2 laser pierced group compared to the spring-loaded gun pierced group. 3 Wound healing was also better in CO2 laser treated sites with less scar contraction compared to scalpel wounds. 3 10,600 nm CO2 laser is absorbed by water resulting in vaporization of intra/extracellular fluid and disintegration of cells.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations